Mobile elements and the genesis of microsatellites in dipterans. - Wilder, J.; Hollocher, H.; Bruno, W.J. (Molecular Biology and Evolution, 2001)
Factors that influence the genesis and genomic distribution of microsatellite DNA are poorly understood. We have identified a novel class of Dipteran mobile elements, mini-me elements, which help elucidate both of these issues. These retroposons contain two internal proto-microsatellite regions that commonly expand into lengthy microsatellite repeats. These elements are highly abundant, accounting for approximately 1.2% of the Drosophila melanogaster genome, giving them the potential to be a prolific source of microsatellite DNA variation. They also give us the opportunity to observe the outcomes of multiple microsatellite genesis events (initiating from the same proto-microsatellite) at separate mini-me loci. Based on these observations, we determined that the genesis of microsatellites within mini-me elements occurs through two separate mutational processes: the expansion of preexisting tandem repeats and the conversion of sequence with high cryptic simplicity into tandemly repetitive DNA. These modes of microsatellite genesis can be generalized beyond the case of mini-me elements and help to explain the genesis of microsatellites in any sequence region that is not constrained by selection.